Primary cilia are sensors of electrical field stimulation to induce osteogenesis of human adipose‐derived stem cells. Issue 1 (19th October 2016) - Cai, Shaobo; Bodle, Josephine C.; Mathieu, Pattie S.; Amos, Alison; Hamouda, Mehdi; Bernacki, Susan; McCarty, Greg; Loboa, Elizabeth G.
Abstract : In this study, we report for the first time that the primary ciliumacts as a crucial sensor for electrical field stimulation (EFS)–enhanced osteogenic response in osteoprogenitor cells. In addition, primary cilia seem to functionally modulate effects of EFS‐induced cellular calciumoscillations. Primary cilia are organelles that have recently been implicated to play a crucial sensor role for many mechanical and chemical stimuli on stem cells. Here, we investigate the role of primary cilia in EFS‐enhanced osteogenic response of human adipose‐derived stem cells (hASCs) by knocking down 2 primary cilia structural proteins, polycystin‐1 and intra flagellar protein‐88. Our results indicate that structurally integrated primary cilia are required for detection of electrical field signals in hASCs. Further more, by measuring changes of cytoplasmic calcium concentration in hASCs during EFS, our findings also suggest that primary ciliamay potentially function as a crucial calcium‐signaling nexus in hASCs during EFS.—Cai, S., Bodle, J. C., Mathieu, P. S., Amos, A., Hamouda, M., Bernacki, S., McCarty, G., Loboa, E. G. Primary cilia are sensors of electrical field stimulation to induce osteogenesis of human adipose‐derived stem cells. FASEB J. 31, 346–355 (2017) www.fasebj.org